Coloring the visual communication of social media instagram within diverse religious madzhabs - Purwani, Diah Ajeng; Antin, Titi; Pratiwi, Fatma Dian; Puspitasari, Niken; Nusa, Lukman (Program Studi Ilmu Komunikasi, 2025)
This article aims to analyze the using of different color in visual communication of social media especially Instagram used by yukngaji communities in Yogyakarta and Riau. These different colors are some kind of representing the different religion madzab that tried to be removed in the realm of unity in diversity and peace. We use virtual ethnography to analyze the content of Instagram accounts @ynjogya and @yukngajipku. The finding of the study indicates that there are three finding related to the research questions. First, the use of dynamic colors. Second, the visualization of religious learning activities, as analyzed in this research, namely the activities of conveying religious teachings by the community via social media is divided into several things. Last, the use of vocabulary containing anti-SARA, such as all forms of preaching content uploaded on social media platforms.